Filtration of aerosol particles by clean elliptical fibers with relevance to pore size: A lattice Boltzmann-cellular automaton model. (12th October 2017) - Lin, Kuang C.; Patel, Ruchik; Tsai, Jeng-Shiun
Highlights: A 2D computational model is used for particle filtration of an elliptical fiber. A correlation between the pore size and an elliptical fiber arrangement is revealed. Particle-fiber collisions can be enhanced while pressure drop decreases. The comparison between an elliptical and a circular fiber is presented. Abstract: Aerosol filtration is fundamental to environmental and industrial applications. Among several computational methods for the estimation of particle-laden flows, the lattice Boltzmann-cellular automata (LB-CA) has shown great promise. After validation, a 2-D LB-CA model is proposed to investigate the effect of pore size on particle-fiber collisions in a laminar free-stream flow over a semi-infinite array of clean elliptical fibers. The study contrasts the particle deposition characteristics of elliptical and cylindrical fibers, towards understanding the effect of ellipse eccentricity and orientation on the particle-fiber collision efficiency. Particle motion mechanisms considered comprise drag, lift, net gravitational and Brownian forces. The results show that the pore size needs to be small enough to show the significant correlation between the particle-fiber collision efficiency and elliptical fiber geometry. In the inertial impaction regime, enhancement of the particle-collision efficiency, reduction of the packing density and decreases of the pressure drop can be simultaneously achieved by employing a high-eccentricity elliptical fiber with an angle of 30° to 90° between the major axis and inflow direction. In the diffusion dominated regime, particle-collision efficiency is found to be influenced only by the fiber surface area.